The effect of dissolved oxygen on the development of manganese oxidizing - and reducing biofilms in the lower blyde irrigation system - Carstens, Alno (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.